2022
DOI: 10.1097/sap.0000000000003104
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biological Scaffold (Biodesign) in Postmastectomy Direct-to-Implant Breast Reconstruction

Abstract: Background: Direct-to-implant (DTI) breast reconstruction is one of the immediate implant-based breast reconstruction methods. If the amount of soft tissue (eg, muscle or fascia) is insufficient to completely cover the implant, biological scaffold or acellular dermal matrix can be safely used for implant coverage. In this study, we used an acellular porcine small intestinal submucosa (SIS) mesh (Biodesign; Cook Medical Inc, Bloomington, IN) for DTI reconstruction to explore the impact of its use on breast rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(61 reference statements)
0
6
0
Order By: Relevance
“… 24 , 25 In recent years, the SIS has been widely used in tissue regeneration engineering and clinical trials for bladder repairing, 26 gastric ulcer repairing, 27 inguinal hernia repairing 28 and breast reconstruction. 29 These studies have confirmed that the SIS possessed great biocompatibility and safety, as well as ability to promote tissue regeneration in vivo, which is essential for diced cartilage grafting. Moreover, the SIS has also been used for cartilage‐related repair and regeneration such as tracheal cartilage regeneration, 30 , 31 meniscal cartilage repairing, 32 , 33 , 34 upper airway regeneration 35 and rheumatoid arthritis repairing.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“… 24 , 25 In recent years, the SIS has been widely used in tissue regeneration engineering and clinical trials for bladder repairing, 26 gastric ulcer repairing, 27 inguinal hernia repairing 28 and breast reconstruction. 29 These studies have confirmed that the SIS possessed great biocompatibility and safety, as well as ability to promote tissue regeneration in vivo, which is essential for diced cartilage grafting. Moreover, the SIS has also been used for cartilage‐related repair and regeneration such as tracheal cartilage regeneration, 30 , 31 meniscal cartilage repairing, 32 , 33 , 34 upper airway regeneration 35 and rheumatoid arthritis repairing.…”
Section: Introductionmentioning
confidence: 75%
“…Small intestinal submucosa (SIS), as a natural decellularised biomaterial consisting of collagen and various growth factors, could promote tissue regeneration, angiogenesis and immunoregulation 24,25 . In recent years, the SIS has been widely used in tissue regeneration engineering and clinical trials for bladder repairing, 26 gastric ulcer repairing, 27 inguinal hernia repairing 28 and breast reconstruction 29 . These studies have confirmed that the SIS possessed great biocompatibility and safety, as well as ability to promote tissue regeneration in vivo, which is essential for diced cartilage grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Decellularized porcine small intestinal submucosa (SIS) ECM was prepared for use as an archetypical ECM scaffold biomaterial and cryogenically milled into an injectable particulate ( Fig 1A ). SIS was selected because it has been extensively studied in soft tissue repair in both pre-clinical and clinical models, including in cancer treatment [7, 8, 25, 26]. An injectable formulation permits minimally invasive localized delivery and avoids the trauma of surgical implantation thus isolating the host response to the ECM scaffold itself ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular matrix (ECM) scaffolds are medical devices derived from decellularized mammalian tissues that are increasingly used biomaterials in cancer care, where they are implanted in patients during reconstructive surgeries immediately following tumor resection [4][5][6][7][8]. ECM scaffolds are immunomodulatory but generate an immune environment that is entirely distinct from the foreign body reaction generated by many synthetic, polymeric scaffold materials.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic and Reconstructive Surgery • January 2024 26e majority of these articles report on retrospective single-center studies with relatively small sample sizes. 3,[16][17][18][19][20] Given the heterogeneity of institution practices, it is difficult to draw concrete conclusions regarding ADM use from these studies. The National Surgical Quality Improvement Program (NSQIP) database is a widely accepted and validated data set that is endorsed by the American College of Surgeons (ACS).…”
mentioning
confidence: 99%